Need Assessment of Teaching Material for Classification Living Things at Junior High School - Riski Amelia; Ermayanti; Meilinda (Postgraduate, University of Mataram, 2025)
This study aims to analyze the need for interactive multimedia-based teaching materials for classifying living things in order to improve students' classification and problem-solving abilities. The research was conducted at SMP Negeri 8 Bayung Lencir using a descriptive method through interviews, observations, and documentation. The research results indicate that the teaching of living organism classification is still teacher-centered, with minimal use of visual and digital media, and has not yet utilized the potential of the surrounding environment. The teaching materials used are limited to textbooks with simple and non-contextual illustrations, which impact the low classification skills and weak contextual problem-solving abilities. The diverse learning styles of students and limited access to biodiversity necessitate varied, interactive, and technology-based teaching materials. The needs analysis shows that students expect teaching materials that are easy to understand (98.82%), interesting (96.47%), contextual (89.41%), independent (81.18%), and technology-based (94.12%). Additionally, 100% of teachers stated the importance of interactive multimedia teaching materials for improving students' classification and problem-solving abilities. The results of this study serve as the basis for the need to develop interactive multimedia-based teaching materials that are relevant to student characteristics and support effective, engaging, and contextual 21st-century science learning.